1992
DOI: 10.1111/j.1365-2672.1992.tb01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized transduction in Bacillus thuringiensis var. aizawai

Abstract: J.R.M. INAL. V. KARUNAKARAN AND H.D. BURGES. 1992. Four temperate phages, ØHD67, ØHD130, ØHD228 and ØHD248, which were isolated from Bacillus thuringiensis H‐serotype 7 strains, were tested for their ability to mediate transduction within H‐serotype 7 and also between H‐serotype 7 and 3a3b. The optimum conditions to facilitate transduction were determined. The four phages successfully mediated transduction within serotype 7 of all five auxotrophic markers tested and thus seem to have the ability to mediate gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Other probably similar phage, φHD248, is described above. Generalized transduction was demonstrated for the φHD248, which confirms that such phages can be useful for limited spectra of hosts (Inal et al 1990(Inal et al , 1992(Inal et al , 1996.…”
Section: Potentially Transducing Phages For the B Cereus Groupsupporting
confidence: 76%
See 1 more Smart Citation
“…Other probably similar phage, φHD248, is described above. Generalized transduction was demonstrated for the φHD248, which confirms that such phages can be useful for limited spectra of hosts (Inal et al 1990(Inal et al , 1992(Inal et al , 1996.…”
Section: Potentially Transducing Phages For the B Cereus Groupsupporting
confidence: 76%
“…The temperate phages φHD67, φHD130, φHD228 and φHD248 isolated after UV-induction from the subspecies aizawai (Inal et al 1990) have been shown to mediate both intra-subspecific ( aizawai) and inter-subspecific ( aizawai-kurstaki) generalized transduction (Inal et al 1992). The phage ϕHD248 was used for genetic analysis of B. thuringiensis subsp.…”
Section: Gene Transduction Experimentsmentioning
confidence: 98%
“…aizawai strains and heterologous transduction between serovars aizawai and kurstaki , were isolated after mitomycin C and UV induction of B. thuringiensis sv. aizawai [ 93 , 94 , 95 ]. Phage genomes sizes were estimated using restriction analyses as follow: ϕHD67: 45,730 bp; ϕHD130: 38,120 bp; ϕHD228: 36,060 bp and ϕHD248: 47,150 bp [ 148 ].…”
Section: Phages Of B Anthracis B mentioning
confidence: 99%
“…Transduction is the transfer of bacterial DNA between cells (intra-or inter-serotype) via transducing phage particles; a technique which is useful for both gene mapping (Heirson, Landen & Boman, 1983) and the production of recombinant strains (Aronson et al ., 1986). Inal, Karunakaran & Burges (1992) demonstrated the transduction of genes between B.t. var.…”
Section: (5) Transduction and Transformationmentioning
confidence: 99%